Resilience: moving from a heroic notion to a sociological concept - Estêvão,Pedro (2017)
This paper presents a specific sociological theoretical framework to the concept of resilience. To do so, we reviewed the main theoretical developments on resilience, focusing our attention on the development of a heroic perspective of resilience. We point out its several pitfalls, and counter it with a concept of resilience grounded on sociological theory and poverty studies, presenting a definition for resilience, the conditions and characteristics of this social phenomenon, as well as a model of operationalization based on two major dimensions: mobilization of resources and shifting of risks. With this innovative approach we also call for a sociological research agenda for resilience.